Pengembangan Buku Ajar dengan Model Addie pada Mata Kuliah Manajemen Teknologi Pendidikan: PENGEMBANGAN BUKU AJAR DENGAN MODEL ADDIE MATA KULIAH MANAJEMEN TEKNOLOGI PENDIDIKAN - Ardiansah, Feri; Miftakhi, Diah Rina (JOEAI (Journal of Education and Instruction), 2020)
This research aims to develop The Teaching Book of Education Technology Management Course to prepare undergraduate students of Elementary School Teacher Education Study Program at STKIP Muhammadiyah Bangka Belitung in managing integrated Thematic learning of elementary schools. The data collection method used is a questionnaire. Data are analyzed with qualitative and descriptive quantitative descriptive techniques. The results showed that the educational technology management textbook developed following the ADDIE Model includes five steps, namely; planning, development, implementation and evaluation. The composition of the teaching book development has followed all five stages of the ADDIE model. The results of research, validation of expert materials related to educational technology management textbooks developed qualified very decent (86.66%) from media experts are also highly qualified (90%), and so are qualified linguists (86.66% ), the average validation result by students on teaching book products is 90.15% (qualifications are very feasible). In conclusion, the overall teaching book of Educational Technology Management Course developed is valid and feasible for use by students. Keywords: Education Technology Management, ADDIE Model, Textbook Development